Islamic law in theory : studies on jurisprudence in honor of Bernard Weiss - Reinhart, Kevin.; Gleave, R.; Sluglett, Peter.; Weiss, Bernard G. (Studies in Islamic Law and Society, 2014)
The contributions of Bernard Weiss to the study of the principles of jurisprudence (uṣūl al-fiqh) are recognized in a series of contributions on Islamic legal theory. These thirteen chapters study a range of Islamic texts and employ contemporary legal, religious, and hermeneutical theory to study the methodology of Islamic law. Contributors include: Peter Sluglett, Ahmed El Shamsy, Éric Chaumont, A. Kevin Reinhart, Mohammad Fadel, Jonathan Brockopp, Christian Lange, Raquel M. Ukeles, Paul Powers, Robert Gleave, Wolfhart Heinrichs, Joseph Lowry, Rudolph Peters, Frank E. Vogel